Viewers’ Perception of Women Portrayal in Cosmetic Commercials on AIT TV Station in Abuja - Otisi, Anaga Onyinyechi; Hope, Gana; Mathias, Musa; K.S., Akpede (Lembaga Yasin AlSys, 2026)
The portrayal of females in television commercials has attracted sustained scholarly attention, particularly in response to feminist critiques of unequal gender representation in the media. In the Nigerian context, women have often been depicted through traditional frames that position them unequally relative to men. This study examined viewers’ perceptions of female portrayal in television commercials broadcast on AIT. Adopting a survey research approach and anchored in perception theory, the study analyzed data using descriptive statistics, specifically frequency and percentage. The findings indicate that stereotypical representations of gender roles, particularly those relating to women, are changing and evolving. Both female and male characters are increasingly portrayed beyond the conventional roles socially assigned to them, suggesting a gradual shift toward more diverse and less restrictive gender representation in television advertising. The study concludes that female portrayal in AIT commercials reflects an emerging departure from traditional gender stereotypes, with implications for more balanced and socially responsive media representation. It therefore underscores the importance of encouraging broader and more equitable portrayals of both genders across product categories to better reflect ongoing societal change.